DEVELOPMENT OF A LEGAL FRAMEWORK FOR THE MANAGEMENT OF ETHICAL AND LEGAL CONFLICTS IN PATIENT CARE - Ginting, Grenaldo; Suningrat, Nining (ANAYASA : Journal of Legal Studies, 2024)
This study aims to investigate the dynamics of ethical and legal conflicts in patient care in Indonesia and to provide recommendations that can enhance clinical practices and healthcare policies. This study employs a qualitative approach by conducting in-depth interviews with healthcare practitioners, patients, and their families. Data is also analyzed through policy analysis and literature review to gain comprehensive insights. The research findings indicate that healthcare practitioners often encounter ethical conflicts in clinical decision-making, especially when their ethical values conflict with the wishes of patients or their families. Ineffective communication among healthcare practitioners, patients, and their families also emerges as a significant factor contributing to conflicts in decision-making. Active involvement of patients and their families in clinical decision-making proves crucial in managing ethical and legal conflicts. Additionally, the uncertainty of healthcare practitioners and resource limitations in handling conflicts also pose significant challenges.